Bibliometric Analysis of the Development of International Accounting Research: A Review of the Literature in the Last Two Decades - Loso Judijanto; Trinandari Prasetya Nugrahanti; Hasan Ashari; Sri Adella Fitri (Westscience Press, 2023)
This research conducts a bibliometric analysis to examine the development of international accounting research over the past two decades. Utilizing a quantitative approach, we explore clusters, highly cited publications, and keyword occurrences within the literature. The analysis reveals six distinct clusters, each highlighting key themes such as challenges in the accounting profession, financial accounting practices, cultural influences, governance dynamics, and value relevance. Additionally, the study identifies highly cited publications that have significantly influenced the international accounting discourse, offering insights into pivotal works that have shaped the field. Keyword analysis further unveils prevalent and less explored themes, with terms like